Induction of apoptosis‐like cell death and clearance of stress‐induced intracellular protein aggregates: dual roles for Ustilago maydis metacaspase Mca1. Issue 5 (16th October 2017) - Mukherjee, Dibya; Gupta, Sayandeep; Saran, N.; Datta, Rahul; Ghosh, Anupama
Summary: Metacaspases primarily associate with induction and execution of programmed cell death in protozoa, fungi and plants. In the recent past, several studies have also demonstrated cellular functions of metacaspases other than cell death in different organisms including yeast and protozoa. This study shows similar dual function for the only metacaspase of a biotrophic phytopathogen, Ustilago maydis . In addition to a conventional role in the induction of cell death, Mca1 has been demonstrated to play a key role in maintaining the quality of the cellular proteome. On one hand, Mca1 could be shown to bring about apoptosis‐like phenotypic changes in U. maydis on exposure to oxidative stress, on the other hand, the protein was found to regulate cellular protein quality control. U. maydis metacaspase has been found to remain closely associated with the insoluble intracellular protein aggregates, generated during an event of stress exposure to the fungus. The study, therefore, provides direct evidence for a role of U. maydis metacaspase in the clearance of the stress‐induced intracellular insoluble protein aggregates. Furthermore, host infection assays with mca1 deletion strain also revealed a role of the protein in the virulence of the fungus. Abstract : Metacaspases are cysteine proteases that usually play key roles in the induction of programmed cell death in protozoa, fungi and plants. There are, however, very few instances available in the literature that report functions other that induction of cell death for metacaspses. In this study, a similar unconventional role of a metacaspase from a biotrophic phytopathogen Ustilago maydis has been demonstrated in addition to a conventional role in apoptosis‐like cell death of the pathogen. Our data shows a key role of U. maydis metacaspse in the protein quality control mechanism of the pathogen. The enzyme through its cysteine protease activity helps in the clearance of insoluble protein aggregates that accumulate during an event of stress exposure of the pathogen. Moreover, the N‐terminal low complexity region of the protein could be demonstrated to regulate the association of U. maydis metacaspase to the aggregates.